The effect of digital citizenship on the quality learning civic education - Alrakhman, Riza; Budimansyah, Dasim; Sapriya, Sapriya; Rahmat, Rahmat (Universitas Negeri Yogyakarta, 2024)
This paper explores the significant roles and influences in the development of responsible technology use and the impact of digital citizenship on the quality of learning within civic education. It begins by hypothesizing that universities play a pivotal role as the primary influencers in shaping an individual's character towards responsible technology usage. The paper emphasizes the need for empirical evidence or authoritative references to substantiate this assertion, thereby highlighting the crucial role of universities in this context. The study then presents statistical evidence indicating a significant relationship between digital citizenship and learning quality in civic education, as highlighted by a t count (14,510) surpassing the t table (1.66) with a significance level of 0.000, lower than the 0.05 threshold. This finding necessitates the backing of its statistical analysis through credible academic sources. Lastly, the paper posits that enhancing digital citizenship will positively influence the quality of learning in civic education, suggesting that this claim should be supported by research or literature in the field. The paper underscores the need for well-supported arguments in discussing the role of university education, digital citizenship, and their impacts on learning quality.